Given data:
Length of peldulum is,
![l_1=L](https://img.qammunity.org/2023/formulas/physics/college/qncso45dj025iczozgrv77ax4282itp132.png)
Period of pendulum is,
![T_1=T](https://img.qammunity.org/2023/formulas/physics/college/h7g4nm28aev521qero516bgvuc34j2kb86.png)
New period of pendulum is,
![T_2=3T](https://img.qammunity.org/2023/formulas/physics/college/q0zwwmrinriybnqwdai5yn7xzfutcjgcw4.png)
Formula:
Formula of period of pedulum is as follows:
![T=2\Pi\sqrt[]{(l)/(g)}](https://img.qammunity.org/2023/formulas/physics/college/57h1imewzd6ipsk7de8u9evrxzsrx5cum1.png)
For old period of pendulum above equation becomes as follows:
![T=2\Pi\sqrt[]{(L)/(g)}](https://img.qammunity.org/2023/formulas/physics/college/zexdae467akfggarjg7rzb89q34rqgjlk9.png)
Taking square of above equation,
![\begin{gathered} T^2=4\Pi^2(L)/(g) \\ L=T^2g(1)/(4\Pi)\text{ ..}.(1) \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/km7af9n0wq2pcdcvic0i2cfe8bskfl7ebk.png)
Now, for new period of pendulum,
![T_2=2\Pi\sqrt[]{(L_2)/(g)}](https://img.qammunity.org/2023/formulas/physics/college/iumq9k4gb741r11q0xt6fnaqeiddq0bsgh.png)
Taking square of above equation,
![T_2=3T^{}_{}_{}](https://img.qammunity.org/2023/formulas/physics/college/crze06kro2x7nx4exltq4pncyr1ly7px0i.png)
Hence,
![\begin{gathered} (3T)^2=4\Pi^2\frac{L_2}{\text{g}}\ldots(2) \\ L_2=9T^2g(1)/(4\Pi)\ldots(3) \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/cvc856mcs7q8owunwh5tnsc0ppxwqz3a61.png)
Taking ratio of equation-(3) and equation-(1),
![\begin{gathered} (L_2)/(L)=9T^2g(1)/(4\Pi)*(1)/(T^2g)4\Pi \\ (L_2)/(L)=9 \\ L_2=9L \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/yugo5f98t6eozfiorfrb6vd05iipfhnum6.png)
Therefore, Length of pendulum should be 9L for the period to be 3T seconds.